(untitled) (European Journal of Marketing and Economics, 2024)
This study constructs a sophisticated economic growth model centered on the gender division of labor and endogenous labor supply, specifically within the framework of nonlinear progressive income taxation. In this model, tax revenue is strategically allocated to the provision of public goods, creating a dual-structure economy composed of a primary production sector and a taxpayer-supported public sector. By integrating these elements, the research effectively describes the complex dynamic interactions between macroeconomic growth, gender-based labor distribution, and progressive fiscal policies. To validate the theoretical framework, the study utilizes numerical simulations to demonstrate the existence of a stable equilibrium and the overall trajectory of the dynamic system. Furthermore, a comprehensive sensitivity analysis is conducted to examine how fluctuations in various parameters influence the long-term motion and stability of the economic system. Ultimately, this work provides critical insights into how tax structures and labor dynamics coalesce to shape the economic evolution and structural equilibrium of modern societies.